Al-Wathaniah fī Syi'ir ilā Ummī lī Mahmūd Darwīsy (al Dirāsāt al Sīmiyāiyyah 'inda Roland Bārthes) - Ashfiyah, Za’imatil; Ulyah, Rika Fithratul; Zaini, Muhammad Ardy (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2022)
This research discusses the patriotism found in Mahmoud Darwish's poetry, entitled